Biotherapeutic bioanalysis: a multi-indication case study review. (March 2011) - Myler, Heather A; Given, Allison; Kolz, Karen; Mora, Johanna R; Hristopoulos, George
A thorough understanding of the structure and biology of a biotherapeutic is crucial to defining a suitable strategy for pharmacokinetic characterization in proof-of-concept disease models, toxicology species as well as the healthy and disease indication patient populations. This manuscript summarizes parameters that impact bioanalytical strategy for over 50 biotherapeutics indicated for the treatment of oncology, rheumatoid arthritis, allergy, multiple sclerosis, hematology, metabolism and infectious disease. We have addressed numerous therapeutic modalities including chimeric, humanized and fully human monoclonal antibodies, replacement proteins, peptides and fusion proteins, including polyethylene glycol and Fc fusions, as well as antibody––drug conjugates. With the rapid evolution of biotherapeutics over the last 20 years and the contraction of the pharmaceutical and biotechnology labor force, efficient workflow management becomes a crucial bioanalytical component. Thus, we have also addressed new technologies that have demonstrated either increased throughput or enhanced characterization, including Meso Scale Discovery, Gyrolab and affinity MS.